2017
DOI: 10.1177/0047287517720118
|View full text |Cite
|
Sign up to set email alerts
|

Tourists’ Emotions as a Resource for Customer Value Creation, Cocreation, and Destruction: A Customer-Grounded Understanding

Abstract: Abstract:Research on customer value creation in a tourism setting has tended to prioritize the firm's over the customer's perspective. However, new understandings of customer value through the lens of customer-dominant logic emphasize the need to consider value as emerging within the broader context of a customer's lifeworld, which transcends customer-firm interactions and includes interactions with others. Tourism experiences are experiential and meaning-laden at the individual and collective levels. As a res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
78
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(80 citation statements)
references
References 67 publications
(107 reference statements)
0
78
0
2
Order By: Relevance
“…The search words "good", "excellent", "great", "nice" and "amazing" were used to capture online visitors' narratives that indicated value co-creation and value co-recovery, while the keywords "awful", "bad", "worst", "terrible" and "poor" were linked to value co-destruction. Research has identified emotions as a key customer resource in the value creation process (Malone et al, 2018). Service encounters, particularly failed ones, often result in negative emotions (Hollebeek & Chen, 2014), further leading to negative outcomes of value co-destruction (Echeverri & Skålen, 2011).…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The search words "good", "excellent", "great", "nice" and "amazing" were used to capture online visitors' narratives that indicated value co-creation and value co-recovery, while the keywords "awful", "bad", "worst", "terrible" and "poor" were linked to value co-destruction. Research has identified emotions as a key customer resource in the value creation process (Malone et al, 2018). Service encounters, particularly failed ones, often result in negative emotions (Hollebeek & Chen, 2014), further leading to negative outcomes of value co-destruction (Echeverri & Skålen, 2011).…”
Section: Data Collectionmentioning
confidence: 99%
“…Service encounters, particularly failed ones, often result in negative emotions (Hollebeek & Chen, 2014), further leading to negative outcomes of value co-destruction (Echeverri & Skålen, 2011). Value co-destruction is founded on negative emotional experiences and has a substantial effect on the customer's well-being (Malone et al, 2018). The 10 keywords helped to avoid generating overwhelming amounts of data.…”
Section: Data Collectionmentioning
confidence: 99%
“…What has not yet been addressed, particularly within travel experiences, is how this sharing, via memory, creates a new collective experience and further opportunities for emotional synchrony and value co-creation. Malone et al's (2018) study begins to address this through customer-dominant logic. They explore value co-creation beyond experience and into the consumer's 'lifeworld' and the importance of emotions within this.…”
Section: Emotions Collective Experience and Communitasmentioning
confidence: 99%
“…TFTLC is a well-known tourist brand in Longquan. Tourist destination brands have been found to follow an attributes-interests-value path [57], such that tourists are 'value-driven' as they seek experiences that can meet their needs, which are based on what they value and how they experienced such value before [58]. The value assessment system used in this study partially refers to Ji's [59] ICH scale.…”
Section: Questionnaire Designmentioning
confidence: 99%